Couple Relationships Homosexual And Heterosexual: A Comparative Study - García, Felipe E. (2017)
The aim of this study was to evaluate and compare heterosexual and homosexual people who are in stable relationships, with respect to the components of the triangular theory of love: conflict resolution tactics, couple adjustment and psychological wellbeing. The participants were comosed of 157 young adults Chileans: 77 homosexuals (30 lesbians and 47 gay men) and 80 heterosexuals (45 women and 35 men). The instruments used were the Dyadic Adjustment Scale, the Sternberg’s Triangular Love Scale, the Flourishing Scale of Diener and Conflict Resolution Style Inventory of Kurdek. The results show that there are significant differences in some conflict resolution tactics, components of love between partners, and couple adjustment according to sexual orientation. In addition, there are also differences between women living and not living with a partner.